PENGARUH MANAJEMEN ASET DAN PROFITABILITAS TERHADAP KINERJA PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Angelina, Melda; Simon, Sharlen; Leonie, Jesslyn (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
Using company size as a moderating variable, this study attempts to evaluate and analyze the impact of profitability and asset management on company performance in raw material sector companies listed on the Indonesia Stock Exchange (IDX) over the 20212023 timeframe. There were 103 companies in the study's population. Purposive sampling was the technique employed, and 156 observation data points were collected from a sample of 52 businesses. The financial statements of companies in the raw material sector that were listed on the Indonesia Stock Exchange for the years 20212023 provided the research data. Partial Least Squares-Structure Equation Modeling with the Path Coefficient test was the data analysis technique employed in this investigation. Additionally, the study's findings show that while profitability has no effect on company performance, the asset management variable does. Additionally, the study's findings demonstrate that the relationship between asset management and profitability and company performance cannot be moderated by company size. This research highlights the value of flexible management techniques in the raw material industry, which is impacted by changes in the price of commodities globally. This report offers useful advice for enhancing asset management, profitability, and business competitiveness.